(untitled) (Bangladesh Journal of Botany, 2019)
Saline-alkali and drought stresses are one of the abiotic stress factors that limit the normal growth and development of plants. In this work, various agronomic indexes including growth physiology and yield attributes were studied under saline-alkali and drought stress treatments. It was found that the limit of plant growth and development caused by drought stress is much higher than that of saline-alkali stress (p < 0.01). Based on the comprehensive evaluation value (D value), under saline-alkali stress condition, 36 maize varieties could be divided into four groups by cluster analysis (CA): High saline-alkali tolerance (3 varieties), medium saline-alkali tolerant(10 varieties), saline-alkali sensitive (19 varieties), high saline-alkali sensitive (4 varieties). In drought stress condition, 36 maize varieties could be divided into five groups by cluster analysis (CA): High drought-tolerance (2 varieties), medium drought-tolerant (14 varieties), low drought-tolerant (15 varieties), drought-sensitive (4 varieties), high drought-sensitive (1 variety). Therefore, this study provides a comprehensive screening of maize varieties under saline-alkali and drought stresses.